A Case of Dilated Cardiomyopathy Associated with 3-Hydroxy-3-Methylglutaryl-Coenzyme A (HMG CoA) Lyase Deficiency - Leung, Alexander A. C. (Hindawi Publishing Corporation, 2009)
3-hydroxy-3-methylglutaryl-coenzyme A (HMG CoA) lyase deficiency is an inborn error of metabolism characterized by impairment of ketogenesis and leucine catabolism resulting in an organic acidopathy. In 1994, a case of dilated cardiomyopathy and fatal arrhythmia was reported in a 7-month-old infant. We report a case of dilated cardiomyopathy in association with HMG CoA lyase deficiency in a 23-year-old man with the acute presentation of heart failure. To our knowledge, this is the first case reported in an adult.